2.45-GHz microwave plasma sources using solid-state microwave generators. ECR-type plasma source. Issue 4 (1st October 2016) - Latrasse, Louis; Radoiu, Marilena; Lo, Juslan; Guillot, Philippe
ABSTRACT: To meet industrial requirements for large-scale processing with high-density and uniform plasma, mandatory for surface treatments to get uniform etching and high deposition rates, we have conceived a new electron cyclotron resonance (ECR) coaxial microwave plasma source which can sustain stable plasmas from 10 −2 Pa to a few Pa, whatever the processing gas, the minimum sustaining microwave power being only a few watt. Furthermore, because the plasma source is powered by its own microwave solid-state generator, multiple ECR plasma sources operating in different conditions of gas type and microwave power can be distributed together in the same reactor. In this design, the solid-state microwave generator produces a forward wave with variable frequency from 2400 to 2500 MHz; this feature is used in an automatic adjustment loop which enables to lower the reflected power created occasionally by changes in the operating conditions. The advantages of the new technology are reported in connection with the plasma scaling-up requirements to distribute uniformly the electric field over large areas. Optical emission spectroscopy and Langmuir probe have been used for the measurement of plasma density, uniformity and electron temperature in argon, oxygen and nitrogen. The results are reported in as a function of the gas type, number of sources and their distribution inside the plasma reactor. The new plasma source enables the production of plasma densities >10 11 cm −3 in all tested gases – Ar, O2, N2, air – at d = 85 mm.